Long term efficacy and persistence of Biologics Therapy in Crohn Disease in Multiracial Asian Country: A real world experience - Nik Muhamad Affendi, Nik Arsyad; Xin Hui, Khoo; leow, alex hwong ruey; hilmi, ida normiha (2023)
NTRODUCTION: Biologic therapy is an effective treatment in moderate-to-severe Crohn disease (CD), however there is a lack of head-to-head randomised control trials to the compare efficacy between available biologic therapy. We sought to determine efficacy and persistence of the currently available therapy in biologic naïve CD patients in our centre. METHODOLOGY: A retrospective, single-centre study was conducted where we recruited all biologic naïve CD patients who were started on biologics therapy- Demographic and baseline clinical characteristic data was collected. Clinical remission and persistence up to 3 years after starting treatment were analysed. RESULT: A total of 118 patients were recruited into this study. Mean age was 30.6 ± 10.9 year old. 61% (n=72) were male and 39% (n=46) were female. Ethnicity, Indian 44.9%(n=53), Chinese 34.7% (n=41) and Malay 19.5% (n=23). Mean disease duration was 7.57 ± 5.1 years. Location of disease was as follows; 34.7% (n=41) Ileal, 28.8% (n=34) colon, 32.2% (n=38) ileocolon and 4.2% (n=5) isolated upper GI. Majority had non-penetrating non-stricturing disease 70.3% (n=83) followed by 17.8% (n=21) stricturing disease and 11.9% (n=14) penetrating disease. 27.1% (n=32) had perianal disease. The median duration of biologic therapy was 26.5 ± 26.8 months. Clinical remission and persistence of biologic therapy are shown in figures 1 and 2 below. CONCLUSION: In this study, infliximab and ustekinumab group have significantly higher efficacy and persistence as compared to adalimumab and vedolizumab although this data has to be interpreted with caution due to the unequal number of patients in each group and retrospective nature of study. A large prospective trial is required.